Exporting capitalism private enterprise and US foreign policy - Kapstein, Ethan B. (Harvard University Press, 2022)
"The US government has long sought investment opportunities for US companies in developing countries. But the results have been mixed: firms have preferred to invest in the industrial world and developing-world leaders have not always welcomed foreign investment. Violence and the presence of natural resources have also hindered foreign development"--Provided by publisher